Laccase immobilization on enzymatically functionalized polyamide 6,6 fibres - Silva, Carla Manuela Pereira Marinho (2007)
Polyamide matrices, such as membranes, gels and non-wovens, have been applied as supports for enzyme immobilization, although in literature the enzyme immobilization on woven nylon matrices is rarely reported. In this work, a protocol for a Trametes hirsuta laccase immobilization using woven polyamide 6,6 (nylon) was developed. A 24 full factorial design was used to study the influence of pH, spacer (1,6-hexanediamine), enzyme and crosslinker concentration on the efficiency of immobilization. The factors enzyme dosage and spacer seem to have played a critical role in the immobilization of laccase onto nylon support. Under optimized working conditions (29 U mL−1 of laccase, 10% of glutaraldehyde, pH = 5.5, with the presence of the spacer), the half-life time attained was about 78 h (18% higher than that of free enzyme), the protein retention was 30% and the immobilization yield was 2%. The immobilized laccase has potential for application in the continuous decolourization of textile effluents, where it can be applied into a membrane reactor.